Diode laser surgery in the treatment of oral proliferative verrucous leukoplakia associated with HPV-16 infection - Gian Paolo Bombeccari; Umberto Garagiola; Valentina Candotto; Francesco Pallotti; Francesco Carinci; Aldo Bruno Giannì; Francesco Spadari (SpringerOpen, 2018)
Abstract Background Proliferative verrucous leukoplakia (PVL) is an oral potentially malignant disorder, characterized by multifocal expression, progressive clinical evolution, and a high rate of malignant transformation. Evidence-based information regarding optimal PVL management is lacking, due to the paucity of data. The present report describes a case of PVL associated with HPV-16 infection and epithelial dysplasia treated by diode laser surgery, and the outcome of disease clinical remission over a 2-year follow-up period. Case report A 61-year-old Caucasian male with oral verrucous hyperkeratosis presented for diagnosis. The lesions were localized on the maxillary gingiva and palatal alveolar ridge. Multiple biopsy specimens have been taken by mapping the keratotic lesion area. Microscopic examination was compatible with a diagnosis of PVL with focal mild dysplasia, localized in the right maxillary gingiva. Polymerase chain reaction (PCR) was done for human papillomavirus (HPV) detection which revealed presence of HPV DNA, and the genotype revealed HPV 16 in the sample. The PVL in the right gingival area was treated on an outpatient basis by excision with a diode laser. This approach resulted in good clinical response and decreased morbidity over a 2-year follow-up period. Conclusions This case illustrates the benefit of a conservative approach by diode laser treatment than wide surgical excision for management of the PVL lesions associated with mild dysplasia and HPV-16 infection.